2004
DOI: 10.1093/bioinformatics/bti201
|View full text |Cite
|
Sign up to set email alerts
|

CLUSTAG: hierarchical clustering and graph methods for selecting tag SNPs

Abstract: mng@maths.hku.hk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 5 publications
0
32
0
Order By: Relevance
“…8 More recently investigation of genetic variation in DAT1 in English and Taiwanese samples suggested that the association is specific to a haplotype of the 10-repeat allele, with the 3-repeat allele of a second VNTR located within intron 8. 31 Analysis of these two markers in this sample revealed the same pattern, with only the 10-3 haplotype showing over transmission from heterozygote parents to their affected offspring (haplotype 34 and rs6347. 38,39 We detected a trend with over transmission of the same allele (A-allele) in rs6347 and no association with rs27072.…”
Section: Dat1mentioning
confidence: 59%
See 1 more Smart Citation
“…8 More recently investigation of genetic variation in DAT1 in English and Taiwanese samples suggested that the association is specific to a haplotype of the 10-repeat allele, with the 3-repeat allele of a second VNTR located within intron 8. 31 Analysis of these two markers in this sample revealed the same pattern, with only the 10-3 haplotype showing over transmission from heterozygote parents to their affected offspring (haplotype 34 and rs6347. 38,39 We detected a trend with over transmission of the same allele (A-allele) in rs6347 and no association with rs27072.…”
Section: Dat1mentioning
confidence: 59%
“…We used the 'CompleteLink routine' within CLUSTAG that implements a hierarchical clustering algorithm (http://hkumath.hku.hk/web/link/CLUS-TAG/CLUSTAG.html. 34 Hierarchical clustering starts with a square matrix of pair-wise distances (as defined by 1-R 2 ) between the SNPs to be clustered. The rationale is that the noncentrality parameter (NCP) for a tSNP is the product of the NCP at the causal SNP and the R 2 .…”
Section: Clinical Proceduresmentioning
confidence: 99%
“…Tagging SNPs were selected using two methods. We used the ''CompleteLink routine'' within CLUSTAG that implements a hierarchical clustering algorithm (hkumath.hku.hk/web/link/ CLUSTAG/CLUSTAG.html) [Ao et al, 2005]. The second method used the default algorithm in Haploview (www.broad.mit.edu/mpg/haploview) from Gabriel et al [2002].…”
Section: Methodsmentioning
confidence: 99%
“…Enhanced Correlation search technique [29] has been applied for clustering gene expression data. CLUSTAG [3], hierarchical clustering and graph based method has been applied for selecting tag SNPs.…”
Section: Introductionmentioning
confidence: 99%